1990
DOI: 10.1021/ja00157a032
|View full text |Cite
|
Sign up to set email alerts
|

New modes of thiophene coordination and reactivity: structures of Cp*Ir(.eta.2-thiophene), an iridathiabenzene, and Cp*Ir(.eta.4-thiophene.cntdot.BH3)

Abstract: The [Cp*Ir(t75-2,5-Me2T)](BF4)2 complex (Id), where Cp* is 7?5-C5Me5 and 2,5-Me2T is 2,5-dimethylthiophene (other thiophenes react similarly), undergoes a two-electron reduction using Na[H2Al(OCH2CH2OMe)2] to give Cp*Ir- (r;4-2,5-Me2T) (2d). Basic Al203 catalyzes the isomerization of 2d to the more stable and novel 3d. X-ray and NMR studies 1d 2d 3dsupport a structure for 3d in which the -system of the six-membered ring is delocalized and may best be described as an iridathiabenzene. Oxidation of both 2d and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(94 citation statements)
references
References 0 publications
2
89
0
2
Order By: Relevance
“…Several metallathiabenzenes have been prepared by insertion of at ransition metal into the CÀSb ond of at hiophene ring. [156][157][158][159] Three possible resonance structures are given in Figure 3. The involvement of as ulfur lone pair (and,t herefore, the degree of p-delocalization about the metallacycle) is highly dependento nt he electron-deficiencyo ft he metal centre.I n general,e lectron-deficient metallathiabenzenes possess delocalized p-systems, although the delocalisation is far less extensive than in metallabenzenes or benzene.…”
Section: Metallabenzynesmentioning
confidence: 99%
“…Several metallathiabenzenes have been prepared by insertion of at ransition metal into the CÀSb ond of at hiophene ring. [156][157][158][159] Three possible resonance structures are given in Figure 3. The involvement of as ulfur lone pair (and,t herefore, the degree of p-delocalization about the metallacycle) is highly dependento nt he electron-deficiencyo ft he metal centre.I n general,e lectron-deficient metallathiabenzenes possess delocalized p-systems, although the delocalisation is far less extensive than in metallabenzenes or benzene.…”
Section: Metallabenzynesmentioning
confidence: 99%
“…Conventionally, thiophene is considered to coordinate poorly to transition metals although there are several recent examples in which M-S(thiophene) distances have been found that are roughly equal to the sum of the covalent radii of divalent sulfur and the metal involved (7)(8)(9)(10)(11)(12)(13)(14)(15). In addition, there are compounds in which weaker interactions occur that can be detected spectroscopically and for which the M-S distance is much longer (16).…”
Section: %mentioning
confidence: 99%
“…In contrast, the main group heteroatom‐containing metallabenzenes are much less developed. The known examples are limited to metallapyrylium,5 metallathiabenzene,6 metallapyridine,7 and metallapyridiniums 7. 8 To the best of our knowledge, metallasilabenzene ( II , Figure 1), formed by the replacement of a carbon atom with silicon in metallabenzene, has never been synthesized although several corresponding silacyclopentadienyl complexes ( I , Figure 1)9 or a nonaromatic analogue ( III , Figure 1)10 have been reported.…”
Section: Introductionmentioning
confidence: 99%